2020
DOI: 10.16930/2237-766220202815
|View full text |Cite
|
Sign up to set email alerts
|

Ativos intangíveis influenciam no desempenho financeiro e no valor de mercado de companhias abertas familiares?

Abstract: O estudo objetivou verificar a influência dos ativos intangíveis no desempenho financeiro e no valor de mercado das companhias abertas familiares, listadas na B3. Para tal, realizou-se pesquisa descritiva, documental e quantitativa. Os dados foram obtidos por meio do Formulário de Referência e do banco de dados Economática, referentes ao período de 2010 a 2017. Para distinguir as companhias familiares, foi rastreada a cadeia de propriedade até identificar o último acionista controlador. Em relação aos ativos i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
3
1
1
Order By: Relevance
“…Regarding the control variables in the estimation with fixed effects, the results are similar to those previously found. Adding that the leverage was shown to have a negative effect on the company's value, that is, the increase in indebtedness decreases the companies' market value, which differs from previous studies that show that leverage has a disciplinary effect on the performance and market value of companies (Araújo et al, 2018;Moura et al, 2020), and liquidity had a positive effect, which denotes that the solvency of the entities is capable of reflecting positively on the market value of the companies (Arrighetti et al, 2014;Moura et al, 2020).…”
Section: Tablecontrasting
confidence: 97%
See 1 more Smart Citation
“…Regarding the control variables in the estimation with fixed effects, the results are similar to those previously found. Adding that the leverage was shown to have a negative effect on the company's value, that is, the increase in indebtedness decreases the companies' market value, which differs from previous studies that show that leverage has a disciplinary effect on the performance and market value of companies (Araújo et al, 2018;Moura et al, 2020), and liquidity had a positive effect, which denotes that the solvency of the entities is capable of reflecting positively on the market value of the companies (Arrighetti et al, 2014;Moura et al, 2020).…”
Section: Tablecontrasting
confidence: 97%
“…The size of the company is a factor that can affect the market value, it is expected that the larger the organization, the greater the control capacity of the entity in generating results that reverberate in return to shareholders, contributing to the appreciation of the organization by the market (Basu et al, 2016;Fosu et al, 2016;Moura et al, 2020). Leverage was included in the proposed model, as it can be considered as a disciplinary mechanism for management and the organization's performance, leveraged companies present greater financial risk, which consequently can cause the market to apply a higher discount rate, which may consequently affect the market value (Araújo et al, 2018;Moura et al, 2020;Viana et al, 2019). The performance of an entity perceived by investors are also aspects that can affect performance and market value (Agyei-Mensah, 2017;Brown et al, 2019;Thakur et al, 2019), so to control the effect of these aspects, liquidity, ROA, and ROE were considered as proxies.…”
Section: Controlmentioning
confidence: 99%
“…We added this data to that published in 2020, the year the pandemic was declared, to identify both the growth and the impact on values, as can be seen in Figure 1. Research: Prepared by the authors Adapted from Brand Finance Global Intangible Finance Tracker (2019, 2020 In Brazil, Moura, Barbosa, Schio and Mazzioni (2020) analyzed the influence of intangible assets on the financial performance and market value of family-owned public companies listed on B3, collecting information from the Economática database from 2010 and 2017. The multivariate analysis revealed that the value of intangibles had a positive influence on the higher market value of companies.…”
Section: Impact Of Covid-19 Pandemic On the Intangible Valuementioning
confidence: 99%
“…Currently, there is an understanding that companies are part of a system related to a numerous group of stakeholders that is not limited by only shareholders and controllers (Okafor, Adeleye & Adusei, 2021). Literature on financial performance has paid attention to the impact of several factors on the performance of organizations, particularly environmental and social responsibility (Okafor, Adeleye & Adusei, 2021), corporate governance (Machado, Prado, Rauber, Carvalho & Santos, 2020), adoption of cutting-edge technologies such as block-chain (Sharma, Shukla & Raj, 2023), exposure to sovereign rating risks (Jesuka & Peixoto, 2022), efficient energy production in emerging markets (Schabek, 2020), management of intangible assets (Moura, Barbosa, Schio & Mazzioni, 2020), the impact of paying bribes to public agents (Jain, 2020), political and economic uncertainties (Hou, Chan, Dong & Yao, 2022), and the action of macroeconomic variables (Juelsrud & Larsen, 2023).…”
Section: The Economic and Financial Performance Of Companiesmentioning
confidence: 99%